A qualitative exploration of English black adults' views of strength and balance activities in mid-life - Nick Cavill; Gill Cowburn; Russell Jago; Charlie Foster (BMC, 2022)
Abstract Background Public health guidelines state that all adults should undertake muscle and bone strengthening and balance training activities at least twice a week to support their physical function and maintain independent health. This is intended to maintain strength in adulthood and offset natural declines in bone density and muscle mass. Most older adults do not meet this guideline with low levels of compliance among older black people. This study explored the experiences of physical activity relating to strength and balance activities, amongst black men and women living in England, aged 50-70. Methods Participants were recruited by phone via a network of research recruitment specialists across England. In-depth qualitative interviews were conducted with 25 black people aged 50-70 living in England. An inductive thematic analysis was conducted. Results We found there was only a very general understanding of the importance of maintaining body strength and balance, and low salience: strength and balance activities were not seen to be an important part of participants' lives. Most participants only wanted to be strong enough to get on with 'normal life' and not to build strength or balance. Participants aged 50-70 were likely to think they were too young to worry about strength and balance, which tended to be mentioned only if someone had experienced a problem. Participants reported that NHS staff, especially physiotherapists are a key source of information on the topic and could therefore be useful in future prevention strategies. Conclusion Public health recommendations stress the importance of increasing participation in regular strength and balance activities as people age, to reduce the risk of falls and maintain independence. This study has shown that among the black middle-aged adults we interviewed, the knowledge and salience of this message is low. Public health approaches should be taken to communicate the importance of enhancing strength and balance as people approach older age, including communication and education programmes led by health professionals, who were viewed with authority amongst these participants.